The effects of sesame oil on the prevention of amiodarone-induced phlebitis - Masoumeh Bagheri-Nesami; Seyed Afshin Shorofi; Seyedeh Zahra Hashemi-Karoie; Alireza Khalilian (Wolters Kluwer Medknow Publications, 2015)
Background: Phlebitis is the most common complication associated with peripheral intravenous infusion of amiodarone. The purpose of this study is to determine the effects of sesame oil on the prevention of amiodarone-induced phlebitis. Materials and Methods: This is a double-blind randomized controlled trial. Thirty-six patients hospitalized in a coronary care unit were randomly allocated into two groups using a convenience sampling method. Following peripheral intravenous cannulation, five drops of pure sesame oil were applied to the skin within a 10 cm radius of the infusion site prior to the administration of amiodarone in the intervention group. Sesame oil was rubbed on the skin at the infusion site every 6 h in the 24-h period of amiodarone infusion. In the control group, liquid paraffin, used as a placebo, was rubbed on the skin at the infusion site of amiodarone. Both groups were monitored for the development of phlebitis and its degree within the 24-h period of amiodarone infusion as well as 6 h after its administration. The incidence of phlebitis was confirmed and recorded by an assessor who was blind to the two groups. Data were analyzed using Statistical Package for Social Science (SPSS) version 18, and descriptive and inferential statistics such as Chi-square test, Kaplan-Meier, Hazard ratio, independent t-test, and Fisher's exact test. Results: There was a statistically significant difference between the two groups in their catheter survival after 30 h and 10 min ( P < 0.001). Over 60% of the patients (61.1%) in the intervention group did not show any sign of phlebitis, while 16.7% and 22.2% of the patients manifested signs of grade 2 and 3 phlebitis, respectively. In the control group, 22.2% of the patients showed no signs of phlebitis, while 5.6%, 27.8%, and 44.4% of the patients exhibited signs of grade 2, 3, and 4 phlebitis, respectively. The statistical analysis showed significant differences in the degree of phlebitis ( P = 0.006) and the onset of phlebitis development ( P < 0.001) between the two groups. Conclusions: It is recommended to apply sesame oil topically to the infusion site of amiodarone so as to reduce the rate of the development of amiodarone-related phlebitis.